Antioxidant and Astroprotective Effects of a Pulicaria incisa Infusion. (23rd December 2012) - Elmann, Anat; Telerman, Alona; Mordechay, Sharon; Erlank, Hilla; Ofir, Rivka
Abstract : Oxidative stress is involved in the pathogenesis of neurodegenerative diseases such as Parkinson's and Alzheimer's diseases. Astrocytes, the most abundant glial cells in the brain, protect neurons from reactive oxygen species (ROS) and provide them with trophic support, such as glial-derived neurotrophic factor (GDNF). Thus, any damage to astrocytes will affect neuronal survival. In the present study, an infusion prepared from the desert plant Pulicaria incisa ( Pi ) was tested for its protective and antioxidant effects on astrocytes subjected to oxidative stress. The Pi infusion attenuated the intracellular accumulation of ROS following treatment with hydrogen peroxide and zinc and prevented the H2 O2 -induced death of astrocytes. The Pi infusion also exhibited an antioxidant effect in vitro and induced GDNF transcription in astrocytes. It is proposed that this Pi infusion be further evaluated for use as a functional beverage for the prevention and/or treatment of brain injuries and neurodegenerative diseases in which oxidative stress plays a role.